Si-Ti interaction in unique morphology of fibrous silica titania photoanode for enhanced photoelectrochemical water splitting. (15th December 2022) - Sawal, M.H.; Jalil, A.A.; Abdullah, T.A.T.; Khusnun, N.F.; Hassan, N.S.; Aziz, F.F.A.; Fauzi, A.A.; Kamaroddin, M.F.A.; Omar, M.F.; Haron, S.
Graphical abstract: Highlights: Fibrous silica titania (FST) was successfully synthesized by microemulsion method. Ti inclusion in Si-matrix induced Si-Ti interaction and enhanced charge separation. Close conduction band to the H2 potential level enhanced the charge transfer in FST. The photocurrent density of the FST photoanode was 2.5-fold higher than TiO2. The FST exhibited exceptional solar-to-hydrogen efficiency of 16.9% Abstract: Extensive efforts toward titania (TiO2 ) modification have been developed in order to overcome the shortcomings as an efficient photoanode for photoelectrochemical (PEC) water splitting. Herein, a unique morphology possessed fibrous silica titania (FST) fabricated by microemulsion method was used for the first time as a photoanode. The FST was characterized by XRD, Raman, N2 adsorption–desorption, FESEM, TEM, FTIR, XPS, UV–vis/DRS, and PL. The results confirmed the creation of a bicontinuous concentric lamellar structure of FST with a high surface area. The inclusions of Ti in the silica matrix induced the Si-Ti interaction and narrowed the band gap. The FST photoanode exhibited a superior photocurrent density of 13.79 mA/cm 2 with 16.9 % solar-to-hydrogen (STH) efficiency, which is 2.5 times higher compared to commercial TiO2 which performed at 5.51 mA/cm 2 with 6.8 % STH. Significantly, the conduction band of FST lies closer to the reduction potential of hydrogen compared to TiO2, leading to the fast charge transfer and allowing spontaneous production of H2 . The fabrication of FST provided new insight into developing high-performance photoanode for enhanced PEC water splitting.